Application of statistical process control charts in business process management - Kosztyán, Zsolt Tibor; Barabás, Bianka; Hegedűs, Csaba; Katona, Attila Imre (Vezetéstudomány / Budapest Management Review, 2025)
Statistical process control (SPC) and control charts are effective tools to monitor and control production processes. SPC is applied not only in manufacturing processes but also in other fields such as healthcare, finance, software development, or education to control the outcome of the tasks. Although business processes (BPs) appear in all fields of the business, no control chart has been developed to monitor and control the whole set of BPs. This paper proposes a new BP control chart (BP chart) and provides a control chart fitting procedure. The proposed method is demonstrated on a real-life BP. Control chart performance is also investigated under nonnormality, and different distribution-free chart statistics are compared to select the best performance for the basis of the BP chart. In terms of practical implications, recommendations are provided for decision-makers regarding the control chart selection for BPs.